Grupos cobertos por seis subgrupos maximais - Alencar, Júnio Moreira de (2011)
This dissertation is based on the article "Groups with a maximal irredundant 6-cover"of A. Abdollahi, MJ Ataei, SM Jafarian Amiri and A. Mohammadi Hassanabadi, which characterize groups with a maximal irredundante cover for six subgroups with core-free intersection. As an application of this result we characterize groups that admit a cover for six subgroups own and does not allow coverage an amount of less than six members. We will also show that the largest index |G : D| over all groups G having an irredundant cover for six subgroup with intersection D is 36.